PENGARUH RASIO PROFITABILITAS DAN LIKUIDITASTERHADAP KEBIJAKAN DIVIDEN PADA PTUNILEVER INDONESIA TBKPERIODE 2011 –2015 (STIE Rajawali Purworejo, 2018)
This study aims to determine the effect of return on equity (ROE) and current ratio (CR ) to dividend payout ratio (DPR). This study uses data analysis methods, multiple regression, coefficient of determination t test and F test. Based on the results of research that researchers do by using SPSS program shows that the correlation test results between ROE variables with House of the amount of - 0.947, while the correlation test results between CR variables with House of equal to - 0.252. In the coefficient of determination obtained results of 0.796 which means that the contribution of ROE and C R variables to the variable of the House is 79.6%, while the remaining 20.4% is explained by other factors not examined in this study. In t test result for ROE variable obtained t count equal to - 4,044, because t count value of ROE smaller than t table (-4,044 <-4,303) hence Ho accepted and H1 rejected so that partially no influence between ROE variable to DPR. While the result of t test for CR variables obtained t count - 0.133, because t count smaller than t table (-0,133 <-4.303) then Ho accepted and H2 rejected sothat partially no influence between variable CR to variable DPR. In the f test results show that the value of f arithmetic of 8.799, because the value of farithmetic smaller than f table (8.799 <19.00) then Ho accepted and H3 rejected,so there is no effect simultaneously between the variables ROE and CR to DPR variables